Photosynthetic Carbon Partitioning and Metabolic Regulation in Response to Very-Low and High CO2 in Microchloropsis gaditana NIES 2587 - Kareya, Mukul Suresh; Mariam, Iqra; Shaikh, Kashif Mohd; Nesamma, Asha Arumugam; Jutur, Pannaga Pavan (Frontiers in Plant Science, 2020)
Photosynthetic organisms fix inorganic carbon through carbon capture machinery (CCM) that regulates the assimilation and accumulation of carbon around ribulose-1,5-bisphosphate carboxylase/oxygenase (Rubisco). However, few constraints that govern the central carbon metabolism are regulated by the carbon capture and partitioning machinery. In order to divert the cellular metabolism towards lipids and/or biorenewables it is important to investigate and understand the molecular mechanisms of the CO2-driven carbon partitioning. In this context, strategies for enhancement of CO2 fixation which will increase the overall biomass and lipid yields, can provide clues on understanding the carbon assimilation pathway, and may lead to new targets for genetic engineering in microalgae. In the present study, we have focused on the physiological and metabolomic response occurring within marine oleaginous microalgae Microchloropsis gaditana NIES 2587, under the influence of very-low CO2 (VLC; 300 ppm, or 0.03%) and high CO2 (HC; 30,000 ppm, or 3% v/v). Our results demonstrate that HC supplementation in M. gaditana channelizes the carbon flux towards the production of long chain polyunsaturated fatty acids (LC-PUFAs) and also increases the overall biomass productivities (up to 2.0 fold). Also, the qualitative metabolomics has identified nearly 31 essential metabolites, among which there is a significant fold change observed in accumulation of sugars and alcohols such as galactose and phytol in VLC as compared to HC. In conclusion, our focus is to understand the entire carbon partitioning and metabolic regulation within these photosynthetic cell factories, which will be further evaluated through multiomics approach for enhanced productivities of biomass, biofuels and bioproducts (B3).